The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5026/jgeography.121.929
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Carbon Isotope Compositions of Hydrocarbon Gas in Neogene Sedimentary Rocks in Horonobe Area, Northern Hokkaido, Japan

Abstract: We conducted headspace gas analyses using cores from two 520 m boreholes to evaluate the gas permeability of Neogene sedimentary rocks in Horonobe, Hokkaido, Japan. Analytical data suggest that most hydrocarbon gases are microbial methane. Further analyses of these data indicated that the low concentration and heavy carbon isotope composition of methane could be explained by carbon isotopic fractionation during migration near fractures. The high residual volume of microbial methane observed in the study area s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Funaki et al . [] reported that the δ 13 C CH4 and C 1 /(C 2 + C 3 ) ratios of a biogenic gas from Neogene sedimentary rocks in the Horonobe area are less than −50‰ and several thousand, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Funaki et al . [] reported that the δ 13 C CH4 and C 1 /(C 2 + C 3 ) ratios of a biogenic gas from Neogene sedimentary rocks in the Horonobe area are less than −50‰ and several thousand, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The d 13 C CH4 and C 1 /(C 2 1 C 3 ) ratios of the gas in the Haboro and Hakobuchi formations, as determined by head-space analysis, are approximately 230& and <10, respectively [JNOC, 1995]; these values indicate that the gases are of thermogenic origin [JNOC, 1995]. Funaki et al [2012] reported that the d 13 C CH4 and C 1 /(C 2 1 C 3 ) ratios of a biogenic gas from Neogene sedimentary rocks in the Horonobe area are less than 250& and several thousand, respectively.…”
Section: Origin Of the Gasmentioning
confidence: 99%
“…The δ 13 C CH4 values of gases from depths of <1000 m, in the biogenic region, are usually in the range of -70‰ to −60‰, with isotopic compositions becoming heavier as depth increases towards the thermogenic region (e.g., [12,13]). Large variations in carbon isotopic ratios in CH 4 and CO 2 are often reported for depths of <1000 m, with δ 13 C CH4 values sometimes reaching −20‰ (e.g., [14][15][16][17]). These variations are associated with the effects of microbial activity on methane production or oxidation in underground environments [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, gas samples from two boreholes (PB-V01 and SAB-1, both~500 m deep) in the Horonobe area, Hokkaido, were processed using IsoJar™ containers [14]. In that study, cores were stored in IsoJar™ containers with water and a few drops of BKC solution [14] for up to three months before headspace analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation